A novel halal and healthy jam product from fruit wastes - Mohamad, Souad A.; Jamal, Parveen (s.n, 2012)

(untitled)
Watermelon waste materials remained one of the important food grade agro-wastes generated by most hospitality industries in Southeast Asia and particularly in Malaysia. Jam was prepared from watermelon rind with different flavours (vanilla, pineapple, strawberry, lemon and no flavour). Five different samples were prepared at various compositions T1 (50-50), T2 (80-20), T3 (60-40), T4 (40-60) and T5 (20-80) of rind and sugar. T1 (50-50) gave the best jam set. Ten man panel (trained) evaluated the jam for its sensory characteristics and physicochemical analysis. Sensory evaluation conducted among five flavours was significantly different at (p>0.05). Chemical analysis showed that ascorbic acid reduced greatly among all treatments during three month storage. Soluble sugar and pH also decreased gradually for T1 (from 4.96 to 4.40), T2 (from 4.92 to 4.21), T3 (from 4.74 to 4.11), T4 (from 4.62 to 4.51) and T5 (from 4.52 to 4.25) upon storage. Strawberry flavoured jam was most acceptable by the panel.